Analisis Faktor-Faktor yang Memengaruhi Tingkat Adopsi Petani Padi dalam Penggunaan Plant Growth Promoting Rhizobacteria (PGPR) (Analysis of Factors Affecting Rice Farmer’s Adoption of Plant Growth Promoting Rhizobacteria (PGPR) Application) - Majid, Thalitha Sabrina Prawidya; Sukadi, Sukadi; Astuti, RR. Siti (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
The use of Plant Growth Promoting Rhizobacteria (PGPR) as a biofertilizer is an alternative fertilization method that can enhance soil fertility and reduce environmental pollution caused by excessive use of chemical fertilizers. This study aims to analyze the influence of age (X1), education level (X2), farming experience (X3), the role of agricultural extension workers (X4), and the role of farmer groups (X5) on the adoption level of PGPR (awareness, interest, evaluation, trial, adoption). The research was conducted in Tirtomartani Village, Kalasan, Sleman, Yogyakarta Special Region, from November 2024 to April 2025, using a quantitative approach through a survey method with questionnaires administered to 38 respondents. The analysis results showed that all independent variables (X) simultaneously had a significant effect on the adoption level of PGPR. However, partially, only the role of farmer groups had a significant influence. Therefore, empowering farmer groups is essential, particularly in raising farmers’ awareness through training on the production and application of PGPR, as an effort to improve their knowledge, attitudes, and skills in using biofertilizers. Keywords: Adoption Rate, Rice Farmer, PGPR.